PERMAINAN TRADISIONAL ENGKLEK UNTUK PENGEMBANGAN MOTORIK KASAR PADA ANAK USIA DINI DI DESA SIMPANG TIGA KABUPATEN KAYONG UTARA - Meti Anggriani; Muhamad Ali; Lukmanulhakim Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to see the traditional game of engklek can develop gross motor skills in early childhood in Simpang Tiga Village, North Kayong Regency. The method used in this research is descriptive method with qualitative research form. The subjects in this study were 5 early childhood and 6 community leaders. The data tool used observation sheets, interviews and documentation. The results showed that: (1) When the child walks and stands long enough to maintain his balance, (2) Running can be done by fostering foot speed and taking stances so that the child can add well to the further ones, (3) ) Jumping can be done by planning in advance and using one leg with the balance adjustment so that at the appropriate time one child's leg does not fall, (4) Throwing can be done by throwing target operations such as distance and weakness so that when throwing it right into the box desired down.Keywords: Engklek Games, Gross Motor Development